WHO WILL TEACH STUDENT TO LIVE? - Semen D. Reznik (Высшее образование в России)
An every ableHbodied citizen of Russia today faces a problem of ensuring his/her competitiveness. This problem especially concerns the graduates of higher education institutions, who often do not focus on the competition, the struggle for their success. This dramatically reduces their chances for successful employment and active professional advancement.The article describes the experiences and results of teaching students the art of competition and special educational technologies aimed at enhancing their social sustainability.